Risk Factors of Strabismus in Southwestern Nigeria - Bello A, Mahmoud AO, Azonobi IR, Adido J, Olatunji FO (Pakistan Journal of Ophthalmology, 2018)
Purpose: The risk factors for strabismus among Nigerian children have not been adequately determined despite the fact that strabismus is a significant cause of visual impairment among them. This study aims to evaluate such risk factors among some Nigerian children. Material and Methods: School pupils aged between 2 and 17 years with manifest strabismus in some randomly selected elementary schools in Ilorin, Nigeria were screened. They were matched with controls comprising of children without ocular misalignment. The studied risk factors included prematurity, low birth weight, family history of strabismus and significant hypermetropia. A full ocular examination of each child included a noncycloplegic refraction using a Topcon 8000R autorefractomter. Results: 7,288 school children were screened. There were 32 cases of strabismus (22 esotropia and 10 exotropia). Of the 32 cases of strabismus, 19 were males and 13 were females. There were 2 cases of significant hypermetropic astigmatism in strabismus group and 1 in controls (P > 0.05, odd ratio 1.0). Significant myopia occurred in 3 cases and in 1 controls (P >0.05, odd ratio 1.5). There were 6 cases of significant hypermetropia in cases and 1 in controls (P <0.05, odd ratio 8.0). There were 12 cases of positive family history in cases and 1 in controls (Odd ratio 19.8 and p<0.05).Prematurity was observed in 18.8% of the cases and 15.6% of controls (P > 0.05,odd ratio of 1.2). Conclusion: There is an association between heredity and strabismus. Significant hypermetropia was found to be a risk factor for strabismus.